Humans Discriminate Individual Zebra Finches by their Song - Sabrina Schalz; Thomas E. Dickins (Biolinguistics, 2021)
Comparative experiments have greatly advanced the field of biolinguistics in the 21st century, but so far very little research has focused on human perception of non-human animal vocalizations. Studies with zebra finch (Taeniopygia guttata) songs found that humans cannot perceive the full range of acoustic cues that zebra finches hear in their songs, although it remained unclear how much individual information is lost. Individual heterospecific discrimination by humans has only been shown with rhesus monkey (Macaca mulatta) voices. The present study examined whether human adults could discriminate two individual zebra finches by their songs, using a forced- choice Same-Different Paradigm. Results showed that adults can discriminate two individual zebra finches with high accuracy and without prior training. Discrimination mostly relied on differences in pitch contour, but discrimination was still possible with lower accuracy when pitch contour was removed. Future studies should expand these findings with more diverse non-human animal vocalizations.